2015
DOI: 10.1038/onc.2015.434
|View full text |Cite
|
Sign up to set email alerts
|

ALK inhibitor resistance in ALKF1174L-driven neuroblastoma is associated with AXL activation and induction of EMT

Abstract: The crizotinib-resistant ALKF1174L mutation arises de novo in neuroblastoma (NB) and is acquired in ALK translocation-driven cancers, lending impetus to the development of novel anaplastic lymphoma kinase (ALK) inhibitors with different modes of action. The diaminopyrimidine TAE684 and its derivative ceritinib (LDK378), which are structurally distinct from crizotinib, are active against NB cells expressing ALKF1174L. Here we demonstrate acquired resistance to TAE684 and LDK378 in ALKF1174L-driven human NB cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 46 publications
3
89
0
Order By: Relevance
“…We found that phosphorylation of AXL was remarkably increased in both H3122-LR and H2228-LR. Consistent with previous reports indicating that AXL was associated with the EMT (10,(20)(21)(22), both LR cells showed EMT-associated morphological changes; specifically, the shape of the cells changed from round to fibroblast-like following the development of treatment resistance (Fig. 1E).…”
Section: Establishment Of An In Vitro Model Of Alk Inhibitor-resistansupporting
confidence: 79%
“…We found that phosphorylation of AXL was remarkably increased in both H3122-LR and H2228-LR. Consistent with previous reports indicating that AXL was associated with the EMT (10,(20)(21)(22), both LR cells showed EMT-associated morphological changes; specifically, the shape of the cells changed from round to fibroblast-like following the development of treatment resistance (Fig. 1E).…”
Section: Establishment Of An In Vitro Model Of Alk Inhibitor-resistansupporting
confidence: 79%
“…AXL-related EMT resulting in drug resistance has been reported in patients with prior EGFR-TKI therapy, as well as in in vitro studies using NSCLC cell lines (15,16,30). Aberrant AXL signaling and the development of the EMT phenotype were also associated with ALK inhibitor resistance in ALK-driven neuroblastoma cells (31). Our clinical data support the concept that EMT under AXL or GAS6 high expression apparently exists in patients with prior surgical resection for lung AD, which consequently leads to de novo resistance to EGFR-TKI (15,30).…”
Section: Univariate Analysis Multivariate Analysissupporting
confidence: 71%
“…The crizotinib-resistant ALK F1174L and ALK R1275Q mutations that arise de novo during crizotinib treatment in NB could result in acquired chemoresistance [10]. Thus alectinib may be very effective treatment option since it induces apoptosis in Kelly and SH-SY5Y, both of which harbor the ALK F1174L mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, alectinib has shown substantial inhibitory effects against tumors with ALK mutations, including ALK L1196M , ALK L1152R , ALK F1174L , and ALK R1275Q [28, 35, 40, 48, 55]. Furthermore, chemoresistant cells harboring crizotinib-mediated ALK mutations ALK F1174L [10, 47] are sensitive to alectinib. Alectinib demonstrated a favorable safety profile and clinically meaningful response in patients with ALK -positive metastatic NSCLC who progressed on crizotinib and, therefore, was granted accelerated approval by the United States Food and Drug Administration (FDA) on December 11, 2015 [25].…”
Section: Introductionmentioning
confidence: 99%